Product design: sports floorings using cork and recycled polymer materials - Cruz, Catarina Ramos da (2022)
The consequences brought by the COVID-19 pandemic are undeniable and shined a light on overwhelming topics that most times humanity just seems to close its eyes to. Research suggests that during this time, the lack of social contact and decrease in physical activities led to psychological disorders such as stress, anxiety, and depression. Since it is a known fact that regular movement and overall active lifestyle, besides the direct health benefits, can help enhance feelings of well being and cognitive function, people started to embrace home workouts and different outside activities (always being considerate of the social restrictions). Even though the pandemic carried some positive environmental impacts due to the limitation of certain activities, resulting in lower levels of pollution, the implementation of behaviours that can combat climate change and other associated issues is imperative. Through Eco-design it is possible to create successful designs that won’t produce as many environmentally negative consequences. Touching on these previous matters and being that it is an exponentially growing market, a project proposal in association with a Portuguese multinational cork company was presented, with the intention of developing two different sports flooring solutions using cork and recycled polymer materials. After researching on associated subjects, the designated materials (including their potential for this product) and solutions already present on the market, dynamic impact and tensile strength tests were performed, which for one of the solutions were inconclusive. For this reason and given the overexploitation of that side of the market that flooring type was abandoned. To further confirm the experimental results, the two best-suited material compositions were tested with users of these floorings, attaining the overall best for the desired goal. Considering different users’ input, and shape exploration, it was possible to achieve a promising solution. The result is different propositions for weight handling flooring tiles, one for commercial use only and the second one, an interlocking modular solution that can be applied whether in a residential or commercial context.